A computational approach to evaluate the pKa's of quinazoline derivatives - Kıran, Melisa. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
One of the most important constants in chemistry is the ionization (dissociation) constant (pKa). Estimating the pKa value(s) for a potential drug is critical, especially since computations are considerably less expensive than obtaining pKa values experi mentally. Nearly 68 % of ionized medicines are said to have weak bases [1]. As a first step in developing an efficient estimation methodology for the pKa of quinazoline and derivatives we studied three protocols. First one is based on the linear relationship between computed atomic charges of quinazoline and derivatives and the experimental pKa. Based on our observations, the optimum method for reproducing observed pKa’s is to compute NPA (Natural Population Analysis) atomic charge using the CPCM (Conductor Like Polarizable Continuum Model) at the M06L/6-311++G** level (R2 = 0.93). The experimental pKa of a collection of quinazoline and derivatives were compared to several Conceptual Density Functional Theory descriptors computed. The highest approximations were observed when employing the M06L/6-311++G** with the CPCM solvation model using water as a solvent. In the final part of our study, M06L/6-311++G** have been used, in combination with CPCM continuum solvent model, to calculate the aqueous pKa values of quinazoline derivatives by using an isodesmic reaction. Possible improvements to current methodology are suggested.
Keywords: Ionization.